Across scales, pronghorn select sagebrush, avoid fences, and show negative responses to anthropogenic features in winter. Issue 5 (7th May 2019) - Reinking, Adele K.; Smith, Kurt T.; Mong, Tony W.; Read, Mary J.; Beck, Jeffrey L.
Abstract: Pronghorn ( Antilocapra americana ) are endemic to western North America where they occupy expanses of grassland and sagebrush ( Artemisia spp.) habitats. The Red Desert region in south‐central Wyoming, USA, has historically served as a stronghold for pronghorn populations, but many herds there have experienced declining population trends over the last two decades, concurrent with oil and natural gas development. These demographic changes and the potential for such energy development, its associated infrastructure, and other anthropogenic features including roads and fences to influence pronghorn habitat selection were the impetuses for our study. We sought to evaluate the potential effect of human‐induced disturbance on multi‐scale seasonal resource selection of 142 adult female pronghorn from 2013 to 2016 using 442 unique animal‐season‐year datasets. We utilized a traditional resource selection function to evaluate seasonal home‐range selection and a step‐selection function to assess fine‐scale, patch‐level seasonal selection. We also compared resource selection during daytime and nighttime hours with step‐selection analyses. At the seasonal home‐range scale, pronghorn selected for areas with more sagebrush during both seasons and areas farther from fences during summer. This trend was also apparent at the patch‐scale level, where pronghorn selected sagebrush‐dominant habitats and avoided crossing fences in all seasons during both day and night. Additionally at this scale, pronghorn selected areas farther from fences during daytime in summer. At the broader, home‐range scale, pronghorn selected areas with greater road density during summer, but with lower road densities and farther from wells during winter. Avoidance of anthropogenic features during winter was also observed at the finer, patch‐scale, with pronghorn selecting for increased density of roads and oil and natural gas wells during daytime in summer, but selecting areas farther from these features during daytime in winter. We recommend minimizing fencing and other forms of anthropogenic disturbance in high‐quality seasonal pronghorn habitats with high proportions of sagebrush, particularly during winter when risk‐avoidance responses may be amplified.